2015
DOI: 10.1302/0301-620x.97b6.33844
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to revisit the AO classification of fractures of the distal radius?

Abstract: We conducted an observational radiographic study to determine the inter- and intra-observer reliability of the AO classification of fractures of the distal radius. Plain posteroanterior and lateral radiographs of 456 patients with an acute fracture of the distal radius were classified by a consultant orthopaedic hand specialist and two specialist trainees, and the k coefficient for the inter- and intra-observer reliability of the type, group and subgroup classification was calculated. Only the type of fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 17 publications
2
20
0
1
Order By: Relevance
“…Unfortunately, none of these classification methods has perfect reproducibility . In contrast to the other classification systems, a strong intra‐ and inter‐observer reliability was reported for the AO/OTA classification when focusing on the main type only (A—extra‐articular, B—partly articular, C—complete articular) . In line with this, we had a consensus rate of 79.7% after classification by two independent investigators and the distribution of the main types of DRFs correlates with previous published papers .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Unfortunately, none of these classification methods has perfect reproducibility . In contrast to the other classification systems, a strong intra‐ and inter‐observer reliability was reported for the AO/OTA classification when focusing on the main type only (A—extra‐articular, B—partly articular, C—complete articular) . In line with this, we had a consensus rate of 79.7% after classification by two independent investigators and the distribution of the main types of DRFs correlates with previous published papers .…”
Section: Discussionsupporting
confidence: 83%
“…Our study has limitations. First, we used the AO/OTA classification, which is only one of many fracture classification systems such as the universal system, the Fernandez classification, the Frykman classification, and the Melone classification . Unfortunately, none of these classification methods has perfect reproducibility .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, 39 % of the residents and 23 % of the surgeons even think it guides neither treatment nor prognosis. This lack of confidence in the classification system is supported by the literature and guidelines, which both state that there is need for a proper classification system which is more user-friendly, has a higher intra- and inter-observer reliability and which guides both treatment and prognosis [4, 10, 11, 28]. Although, CT-scanning of distal radius fractures is becoming more popular, it does not significantly improve the inter- and intra-observer agreement for most classification systems [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies determined the intra- and inter-observer reliability for the most frequently used classification systems and all studies showed a low reproducibility and reliability [511]. Furthermore, it is questionable if these classification systems help to guide treatment and prognosis.…”
Section: Introductionmentioning
confidence: 99%